THE ROLE OF EXPERT WITNESSES IN CRIMINAL TRIALS: ENSURING SCIENTIFIC RIGOR AND LEGAL RELEVANCE - Rupali Sharma, (Chelonian Research Foundation, 2024)
The role of expert witnesses in criminal trials in India is crucial in ensuring the scientific rigor and legal relevance of evidence presented in court. In recent years, the Indian judiciary has recognized the importance of expert testimony in complex cases, particularly those involving scientific and technical evidence. This paper examines the role of expert witnesses in Indian criminal trials, highlighting their significance in ensuring the admissibility and credibility of scientific evidence. In India, the Code of Criminal Procedure (CrPC) and the Indian Evidence Act (IEA) provide a framework for the use of expert witnesses in criminal trials. Section 45 of the IEA defines an expert witness as one who has specialized knowledge or skill in a particular field, which enables him to form an opinion on a matter relevant to the case. The crux of expert testimony lies in its ability to provide objective and unbiased opinions, derived from scientific methods and principles. The paper discusses the challenges faced by expert witnesses in Indian courts, including the need for rigorous cross-examination, potential bias, and conflicting opinions. To address these concerns, the Indian judiciary has developed guidelines for the examination of expert witnesses, such as the use of voir dire to assess their qualifications and impartiality. The paper also highlights the importance of judicial scrutiny in evaluating expert testimony, emphasizing the need for courts to critically analyze the scientific basis of expert opinions and to consider alternative explanations for the evidence presented. Furthermore, it discusses the role of scientific organizations and research institutions in providing expertise to courts and promoting best practices in forensic science. The role of expert witnesses is critical in ensuring scientific rigor and legal relevance in Indian criminal trials. By understanding their role, challenges, and limitations, courts can ensure that expert testimony is credible and reliable, thereby promoting justice and upholding public confidence in the criminal justice system